The Influence of Social Media and Brand Image on Repurchase Intention Mediated By Customer Satisfaction (An Empirical Study Of Consumers of Roman Brand Ceramic Tiles In Jakarta) - Albertus Febi AP; Liem Bambang Sugiyanto (Publikasi Indonesia, 2024)
The objective of this study is to investigate the impact of social media and brand image on repurchase intention, while also examining the role of customer satisfaction as a mediating variable among consumers of Roman ceramic tiles brand in Jakarta. This research was conducted using online and offline methods to 134 respondents with the criteria of being or having been a Roman brand ceramic tile consumer in Jakarta. This study uses a quantitative approach using structural equation models and is processed using AMOS 24 software. The results also show that social media and brand image have a positive and significant effect on repurchase intention mediated by customer satisfaction. Based on the results of the study, it can be concluded that both independent variables and mediating variables can maximally increase consumer repurchase intention for Roman brand ceramic tile consumers in Jakarta. The limitation of this research is that the survey was conducted on Roman ceramic tile consumers in Jakarta and the survey period was only carried out for one month, and the respondents in this study were only consumers who live in the Jakarta area. This study seeks to understand the effect of social media and brand image on repurchase intention mediated by customer satisfaction. The results of this study are expected to provide insight for marketers and manufacturers in designing social media strategies and brand image to increase repurchase intention.